THE EFFECT OF ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURAL INTENTION (Study on Students of Class XII SMKN 5 Madiun, Academic Year 2017/2018) - Eka Restianingsih; M. Kholid Mawardi (Jurnal Administrasi Bisnis, 2019)
Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan pendidikan kewirausahaan dan menganalisis pengaruh pendidikan kewirausahaan terhadap niat kewirausahaan siswa kelas XII Tahun Ajaran 2017/2018 di SMK Negeri 5 Kota Madiun. Penelitian ini merupakan penelitian explanatory dengan pendekatan kuantitatif. Populasi penelitian adalah siswa Kelas XII Negeri 5 Kota Madiun Tahun Ajaran 2017/2018.Kuesioner didistribusikan kepada 61 responden dengan metode simple random sampling. Penelitian ini menggunakan teknik analisis regresi linier sederhana dan analisis deskriptif. Berdasarkan perhitungan analisis regresi linier sederhana, menunjukkan bahwa pendidikan kewirausahaan berpengaruh terhadap niat kewirausahaan. Oleh karena  itu SMK Negeri 5 Madiun sebaiknya mempertahankan dan menigkatkan variabel pendidikan kewirausahaan tidak hanya melalui mata pelajaran, namun implementasi dilakukan dengan berbagai bentuk media pembelajaran berbasis produksi dan bisnis antara lain: Teaching factory, Teaching industry, Hotel training, Incubator business dan Business Center di sekolah. Keywords: Teori Kewirausahaan, Pendidikan Kewirausahaan, Niat Kewirausahaan. ABSTRACT This study aims to describe the implementation of entrepreneurship education and analyze the influence of entrepreneurship education on entrepreneurship intention of students class XII, academic year 2017/2018 at SMK Negeri 5 Madiun. This research is an explanatory research with quantitative approach. The population of this research is the students of Class XII SMK Negeri 5 Madiun in the academic year of 2017 / 2018. Questionnaires were distributed to 61 respondents by simple random sampling method. This research uses simple linear regression analysis technique and descriptive analysis. Based on the calculation of simple linear regression analysis, indicating that entrepreneurship education has an effect on entrepreneurial intention. Therefore SMK Negeri 5 Madiun should maintain and improve the entrepreneurship education variables not only through the subjects, but the implementation is done with various forms of learning media based on production and business, among others: Teaching factory, Teaching industry, Hotel training, Incubator business and Business Center in school. Keywords: Entrepreneurship Theory, Entrepreneurship Education, Entrepreneural Intention.